Rotor and Structural Dynamics of Turbomachinery A Practical Guide for Engineers and Scientists - Subbiah, Raj (Applied Condition Monitoring,, 2018)
This book provides engineers and scientists with practical fundamentals for turbomachinery design. It presents a detailed analysis of existing procedures for the analysis of rotor and structure dynamics, while keeping mathematical equations to a minimum. Specific terminologies are used for rotors and structures, respectively, allowing the readers to clearly distinguish between the two. Further, the book describes the essential concepts needed to understand rotor failure modes due to lateral and torsional oscillations. It guides the reader from simple single-degree-of-freedom models to the most complex multi-degree-of-freedom systems, and provides useful information concerning steel pedestal stiffness degradation and other structural issues. Fluid-film bearing types and their dynamical behavior are extensively covered and discussed in the context of various turbomachinery applications. The book also discusses shaft alignment and rotor balancing from a practical point of view, providing readers with essential information to help them solve practical problems. As the main body of the book focuses on the diagnostics and description of case studies addressing the most pressing practical issues, together with their successful solutions, it offers a valuable reference guide, helping field engineers manage day-to-day issues with turbomachinery.